A rare case of giant uterus like mass arising from broad ligament: a case report with review of histogenesis (Indian Journal of Case Reports, 2017)
The uterus-like mass (ULM) is an anatomical entity first described in the ovary and thereafter, reported in several locations of the pelvis and abdominal cavity including broad ligament, greater omentum, cervix, small intestine, mesentery and conus medullaris. It is characterized by a miniature uterus comprising a smooth muscle wall lined by endometrium; thus, delineating a uterus-like anatomical structure. A 46-year-old lady presented with swelling in the abdomen. Imaging studies showed a thick walled cystic lesion in the pelvis and histopathology revealed a uterus like mass reminiscent of uterine morphology with its characteristic inner endometrium and outer smooth muscle. This entity is very uncommon with only few cases reported in literature. This case is being highlighted for its rarity and to discuss the possible theories for origin of this uncommon condition.